Coordination polymers and supramolecular solid-state architectures constructed from an organometallic tecton, bis(4-pyridyl)mercury. (1st July 2019) - Mocanu, Teodora; Kiss, Levente; Sava, Alexandru; Shova, Sergiu; Silvestru, Cristian; Andruh, Marius
Graphical abstract: Four new 1-D coordination polymers have been assembled using an organomercury spacer. The solid state architectures are supported by various weak interactions in which the mercury atom is involved. A new system resulted from the co-crystallization of bis(4-pyridyl)mercury with a binuclear copper(II) complex is described. Abstract: Four new 1-D coordination polymers have been assembled using bis(4-pyridyl)mercury (py2 Hg) as spacer: 1 ∞ [Mn(hfac)2 (py2 Hg)]1, 1 ∞ [Zn(CH3 COO)2 (py2 Hg)]∙2H2 O2 ; 1 ∞ [Ni(dipdtp)2 (py2 Hg)]3 (dipdtp = O, O′-diisopropyldithiophosphato), 1 ∞ [Zn(H2 O)4 (py2 Hg)]∙(18C6)(ClO4 )2 4 (18C6 = crown ether 1, 4, 7, 10, 13, 16-hexaoxacyclooctadecane). The crystal structures of1, 3, and4 consist of linear chains, while2 shows a zigzag topology. The zigzag chains in2 are assembled into supramolecular layers through weak Hg⋯O interactions, and are further linked into a 3-D framework by tetrameric water clusters. The structure of3 is expanded into 2-D layers through weak Hg⋯S interactions. In crystal4, the 18C6 molecules act as second coordination sphere ligands. The supramolecular 3-D network is sustained by hydrogen bonds and Hg⋯O interactions. The system [Cu2 (valpa)2 ]∙(py2 Hg)5 was obtained from a co-crystallization process of py2 Hg and the binuclear complex [Cu2 (valpa)2 ] (H2 valpa is the Schiff base resulted from the condensation reaction between o -vanillin and propanolamine). The py2 Hg molecules in5 interact each other through N⋯Hg bonds generating layers with square meshes. The organometallic tecton, through the mercury atom, is involved in various weak interactions (Hg⋯O, Hg⋯N, Hg⋯S), which play an important role in sustaining the solid state architectures.